2017
DOI: 10.1177/1533034617709596
|View full text |Cite
|
Sign up to set email alerts
|

Transabdominal Ultrasonography-Defined Optimal and Definitive Bladder-Filling Protocol With Time Trends During Pelvic Radiation for Cervical Cancer

Abstract: Purpose:Advanced radiotherapy techniques have emphasized on the importance of accurate target volume localization and delineation. The aim of this study was to determine time taken to achieve moderate bladder volume under physiological conditions, using transabdominal ultrasound.Materials and Methods:Patients with cervical cancer undergoing radical radiation with or without concomitant chemotherapy underwent serial ultrasound to estimate bladder filling. With a strict bladder protocol of consuming 1000 mL of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Umesh et al performed a cohort study of patients treated with cervical radiotherapy. 47 They found that a 300 mL bladder volume was tolerable throughout treatment and was achieved after a mean time of 65 minutes following bladder emptying and administration of 1,000 mL of water. A further benefit from ultrasound is the potential to reduce radiation dose from additional CBCT scans.…”
Section: Rectal Spacersmentioning
confidence: 99%
See 1 more Smart Citation
“…Umesh et al performed a cohort study of patients treated with cervical radiotherapy. 47 They found that a 300 mL bladder volume was tolerable throughout treatment and was achieved after a mean time of 65 minutes following bladder emptying and administration of 1,000 mL of water. A further benefit from ultrasound is the potential to reduce radiation dose from additional CBCT scans.…”
Section: Rectal Spacersmentioning
confidence: 99%
“…This approach is supported by an RCT by Mullaney et al of two different drinking protocols in prostate radiotherapy. The group found that 540 ml (3 cups of water over 10 minutes) was associated with better reproducibility of bladder volume as assessed by bladder ultrasound than 1080 ml (6 cups of water over 10 minutes) [42]. Studies of ultrasound bladder scanning have reported improved consistency of bladder volume during prostate radiotherapy [43][44][45].…”
Section: Bladder Filling Protocolsmentioning
confidence: 99%